Effects of lupin incorporation on the physical properties and stability of bioactive constituents in muffins - Rumiyati, R.; James, A.; Jayasena, Vijay (Blackwell Publishing Ltd, 2015)
Summary: Germinated Australian sweet lupin (ASL) flour (after germination for 7 days) was incorporated into muffin formulation at 0%, 2%, 4%, 6% and 8% of dried muffin weight. The effect on the physical characteristics of muffins including height, diameter, colour and texture (hardness, cohesiveness, springiness and chewiness) was measured. The stability of phenolic, phytosterol compounds and the antiradical activity of the muffins before and after baking (190 °C, 25 min) were determined. The level of incorporation of germinated ASL flour affected the volume, colour, hardness and muffin texture. Muffins incorporated with germinated ASL flour at the levels used in this research exhibited higher concentrations of total phenolic compounds, phytosterol and antiradical activity than those in control muffins. The baking process did not significantly reduce the phenolic compounds, phytosterol and antiradical activity.